El comercio justo y la inclusión económica de los comerciantes informales de los mercados de Riobamba - Basantes Ávalos,René Abdón (2023)
ABSTRACT: The present research entitled "Fair Trade and the Economic Inclusion of Informal Traders in the Markets of Riobamba" aims to determine how fair trade influences the economic inclusion of informal workers in Riobamba's markets. To carry out this research were used field, descriptive and explanatorys' methodologies, which were suitable for its elaboration. In addition, surveys were conducted to 348 informal traders in Riobambas' the markets, with open and closed questions allowing for ease response. We used a non-experimental methodology, which was done without changing its variables to conduct the research. At the end of this research, it revealed that both fair and informal trade face considerable challenges related to ethical awareness, transparency, equity and sustainability. In the markets located in Riobamba, Informal workers face socioeconomic hardships, such as precarious working conditions and lack of access to essential labor benefits. These findings highlight a marked lack of equity and fairness in both forms of trade, as fair trade seeks to promote fair conditions for producers, while informal traders struggle for inclusion in the formal economic system.